Scrappy little nobody - Kendrick, Anna (Touchstone, 2016)
"A collection of whimsical autobiographical essays by the Academy Award-nominated actress and star of Up in the Air recounts memorable milestones from her New England upbringing to the blockbuster films that have made her one of Hollywood's most popular actresses,"--Baker & Taylor.